Method of S Wave Identification: Application to Measured blasting vibration signals. Issue 4 (October 2020) - Yang, Zhaowei; Hu, Yinguo; Liu, Meishan; Wu, Xinxia; Zhao, Gen
Abstract: S wave identification is an indispensable step in the process of deriving the dynamic parameters of rock masses, which are highly significant in guiding the design and construction of hydraulic engineering projects. However, it is difficult to identify S waves accurately because of 1) the influence of overlapping within the P wave coda and 2) the incomplete separation between S and P waves owing to the characteristic short distances of blasting seismic wave propagation. This paper presents a modified method for accurately identifying S waves at the engineering scale using blasting vibration signals. The proposed method combines the application of the short-time average zero-over rate with polarization analysis. By using the short time average zero-over rate, it is possible to effectively reduce the computational time while improving the computational efficiency. Polarization analysis is used to improve the accuracy of the method. A comparison of numerical identification and theoretical results revealed that the improved method is clearly capable of S wave identification with errors of less than 2%. To demonstrate the capability and accuracy of the proposed method, measured vibration signals were introduced to the Fengning pumped-storage power station and the S wave velocities obtained from the first arrival times were compared to obtain an estimated S wave velocity.